Transcutaneous electrical nerve stimulation (TENS) in the treatment of postoperative pain and prevention of paralytic ileus - (:unkn) unknown (My University, 1993)
This study was performed on 30 patients who had undergone various gynaecological operations. Transcutaneous electrical nerve stimulation (TENS) was used on 17 patients and placebo TENS on the remaining 13. Pain severity, the need for analgesic drugs and the presence of paralytic ileus were evaluated in all patients during the first three postoperative days. There was no significant difference in pain severity between the two groups in the immediate postoperative period (p > 0.5). However, evaluations performed at the end of the first, second and third postoperative days revealed a very significant difference in pain severity (p < 0.01) and analgesic drug use in the two groups. A comparison of postoperative complications showed paralytic ileus in seven patients in the placebo group (54%); only two patients in the TENS group (12%) showed the same symptoms. Significant analgesia, an important reduction in analgesic drug use and a decrease in the incidence of paralytic ileus were observed as a result of the application of TENS in the postoperative period. © 1993, Sage Publications. All rights reserved.